Design And Implementation Of Customer Satisfaction Analysis In Pdam Surya Sembada Surabaya - Oktavianus Eko Pambudi Adi Nugroho; Sulistiowati Sulistiowati; Yoppy Mirza Maulana (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Regional Water Company (PDAM) Surabaya is an engaged  instantion in the field of public service. One of the company's mission is to provide superior service to its customers. Thus the analysis of customer satisfaction becomes important to know whether a given service in accordance with the wishes of the customer. There is the problem based on the analysis of customer satisfaction. It is how to analyze customer satisfaction and generate a report that will be used as a repair and improvement of customer service quality. Analysis of customer satisfaction application is the solution to these problems, where the application can perform in the process of surveying, data analysis, and reporting of analytical results. Customers can fill a questionnaire online, after that the data collected will be analyzed by using a characteristics calculation system, satisfaction index, and the importance of performance analysis. the analysis results will be a reported  and will be used by  the management of PDAM Surabaya  as an evaluation of service quality.